2004
DOI: 10.1088/0953-8984/16/15/022
|View full text |Cite
|
Sign up to set email alerts
|

Infrared, Raman and high-frequency dielectric spectroscopy and the phase transitions in Na1/2Bi1/2TiO3

Abstract: Infrared reflectivity, time-domain terahertz transmission, high-frequency dielectric measurements and Raman spectroscopy of Na0.5Bi0.5TiO3 complex ferroelectric perovskite were performed in a broad temperature range. The results were analysed considering the macroscopic symmetry as well as symmetry resulting from local Na–Bi ordering in all three known phases. An overdamped infrared soft mode was revealed in the THz range which, together with central-mode type dispersion in the GHz range, contribute to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
108
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 39 publications
20
108
0
Order By: Relevance
“…The spectrum is consistent with previous reports, 15,[21][22][23][24] where it was assigned as belonging to the pseudo-rhombohedral R3c phase, for which a total of 13 Ramanactive modes (Γ Raman, R3c =4A 1 +9E) are expected. 23 Three main regions can be discerned. The first one at ~270 cm -1 is dominated by an A 1 mode assigned to Ti-O vibrations.…”
Section: Raman Spectroscopy Of Unmodified and Fe-modified Nbtsupporting
confidence: 91%
See 1 more Smart Citation
“…The spectrum is consistent with previous reports, 15,[21][22][23][24] where it was assigned as belonging to the pseudo-rhombohedral R3c phase, for which a total of 13 Ramanactive modes (Γ Raman, R3c =4A 1 +9E) are expected. 23 Three main regions can be discerned. The first one at ~270 cm -1 is dominated by an A 1 mode assigned to Ti-O vibrations.…”
Section: Raman Spectroscopy Of Unmodified and Fe-modified Nbtsupporting
confidence: 91%
“…[16][17][18][19] Raman spectroscopy has been used to study phase transitions and the nanoscale structural characteristics of NBT and its solid solutions. 15,[20][21][22][23][24] Due to challenges of intrinsic broadening and overlapping of phonon modes in the assignment of mode symmetries, structural analysis thus relies on analyzing soft-mode or hard-mode behavior as a function of composition, pressure or temperature. 15,[21][22][23][24] Other studies in NBT-BT 25 and NBT-SrTiO 3 24 generally confirmed that transitions involving the ferroelectric behavior are related to subtle local structural distortions and phase coexistence.…”
Section: As Well Asmentioning
confidence: 99%
“…It means that, besides the induced polarization, P i (E) contains other relevant contributions, such as reorientation and breathing of PNR [45]. Earlier, the breathing mechanism was used to interpret the frequency dispersion of dielectric permittivity in NBT at low temperatures [46]. Remarkable reduction of T(P i ) slope upon decreasing of temperature, expressed in Figure 4 as T/P i as a function of E, can be attributed to PNR breathing mechanism, extended to moderate electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium bismuth titanate, Na 1/2 Bi 1/2 TiO 3 (NBT), is known to be a typical relaxor perovskite and has been extensively investigated for its potential applications to actuators, sensors, and transducers (Siny et al, 1991;Tu et al, 1994;Kreisel et al, 2000;Xu & Ching, 2000;Kreisel et al, 2001;Petzelt et al, 2004;Dorcet & Troillard, 2008) C. More interestingly, the broad frequency dependent permittivity vs. temperature in NBT strongly arise the possibility of its relaxor ferroelectricity even though the large coercive electric field and remnant polarization in NBT imply the strong ferroelectricity at room temperature. The relaxor behavior in complex perovskite oxides has been mostly studied in lead-based perovskites such as Pb(Mg 1/3 Nb 2/3 )O 3 , Pb(Sc 1/2 Ta 1/2 )O 3 and Pb 1-x La x (Zr y Ti 1-y ) O 3 (Smolenskii et al, 1961a;Chu et al, 1993;Dai et al, 1994;Krunmins et al, 1994); relaxor property is explained to be attributed to nano polar cluster with a cationic ordering, which is embedded in the nonpolar matrix with a cationic disordering.…”
Section: Introductionmentioning
confidence: 99%